Pengaruh Lingkungan Kerja, Budaya Organisasi, dan Motivasi Kerja terhadap Produktivitas Kerja Karyawan pada Kantor Dinas Kesehatan Kota Yogyakarta - Selviana Wulang Wuran; Didik Subiyanto; Epsilandri Septyarini (Jurnal Bingkai Ekonomi (JBE), 2021)
This study aims to determine whether the work environment, organizational culture and work motivation have a positive and significant effect on the work productivity of employees of the Yogyakarta City Health Office. The population in this study were all employees who worked at the Yogyakarta City Health Office as many as 50 people. In this study, researchers used a saturated sampling technique, namely a sampling technique if all populations were sampled. The data collection method used a questionnaire. The analysis technique used is regression with a significant level of 0.05. The results of this study indicate that: 1). The work environment has a positive and significant effect on employee work productivity. 2). Organizational culture has a positive and significant effect on employee work productivity. 3). Work motivation has a positive and significant effect on employee work productivity. 4). Work environment, organizational culture, and work motivation have a positive and significant effect on employee work productivity.